Analysis and Implementation of a High Boost Ratio DC-DC Converter for Minimizing Commutation Torque Ripple in Brushless DC Motor - M. Senthil Raja; B. Geethalakshmi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
Brushless dc motor still suffers from commutation torque ripple, which primarily depends on transient line current in the commutation interval. In order to control the incoming and outgoing phase currents to change at the same rate during commutation, this paper presents a novel high boost ratio DC-DC circuit topology in the front end of the inverter. With a suitable closed loop control scheme, the proposed high boost ratio DC-DC converter is operated with two different duty ratios one during commutation period and the other during non commutation period. The cause of commutation ripple is analyzed, and the way to adjust the duty ratio for obtaining the desired dc link voltage is introduced in detail. Finally, simulation and experimental results show that, compared with the existing dc–dc converter topologies, the proposed method can obtain the desired voltage much faster and minimize commutation torque ripple more efficiently